E-Version - Prof. Louis Egwari, Editor-in-Chief; Edwin O. Agbaike, Managing Editor: (Covenant Journal of Physical and Life Sciences, 2018)
All rights reserved. No part of this publication may be reproduced, stored in a retrieval system or transmitted in any form or by any meams, electronic, electrostatic, magnetic tape, mechanical, photocopying, recording or otherwise, without the prior written permission of the publisher.